Effect of NiO, ZrO2 and TiO2 on the formation of glass-ceramic cordierite in the MgO–Al2O3–SiO2–MoO3 system - Manuela Alejandra Zalapa-Garibay; Simón Yobanny Reyes-López (Journal of Materials Research and Technology, 2024)
In glass-ceramic design, the two most crucial factors are composition and microstructure both factors control the ability to form a glass and determines its degree of workability. The composition also determines whether internal or surface nucleation can be achieved. If internal nucleation is desired, as is the case in hot forming glassware, right nucleating agents are melted into the glass as part of the bulk composition. For this reason, this research work focuses on obtaining glass-ceramic cordierite starting from a parent glass of the MgO–Al2O3–SiO2–MoO3 system, using NiO, ZrO2 and TiO2 in a range of 1%Wt to 3%Wt, with the objective of identifying which of the oxides most favors the formation of cordierite. Twelve samples were prepared, which were characterized by thermal gravimetric analysis (TGA), differential thermal scanning analysis (DSC), X-ray diffraction (XRD), Elemental X-ray mapping (SEM), and Infrared spectra using the ATR technique (FT-IR). It was found that NiO is the oxide that most promotes the formation of the cordierite phases, in addition to the use of molybdenum as part of the parent glass, which lowers the crystallization temperature of the crystalline phases obtained. This is determined with the results of phase quantification using the Rietveld method, by XRD, where the samples with NiO add up to a content greater than 90 % of cordierite α and β. And it is supported by the SEM results, where the characteristic hexagonal morphologies of cordierite are identified, the IR characterization results where the bands of the bonds of the phases identified by XRD are identified.